Pengaruh Branderpreneurship Mindset Terhadap Intensi Pelaku UMKM Dalam Menggunakan Teknologi E-Commerce - Sania Christie; Deni Hadiana; Andreas Corsini Widya Nugraha (Global Sustainability Research Institute, 2024)
Introduction: This research aims to find out the influence of a branderpreneurship mindset on the intensity of MSMEs perpetrators in the use of technology. A branderprenuership mindset is an individual's attitude in using strategies to harness opportunities that focus on brand development.Methods: This research uses quantitative methods, which use studies of regression and correlation tests. The population that the researchers used for the research was the MSMEs perpetrators who resided in the city of Bekasi. Sampling using quantitative techniques. This study has 189 respondents that will be used by researchers.Results: According to Spearman's correlation analysis rho obtained the value of the correlation coefficient of 0.852, this value refers to the positive influence between branderpreneurship mindset and intensity. The positive value indicates that the higher the value branderprenuership mindset, the higher the intensity, and instead the lower the intensity is, the lower the brandepreneurships mindset. Umkm actors with a branderpreneurship mindset tend to have a better level of intensity in innovating and building greater confidence. It was further obtained that the branderpreneurship mindset played a role in the influence of 95.4% against the intensity of MSMEs perpetrators in Bekasi city.Conclusion and suggestion: Stated alternative hypothesis (ha) accepted. The higher the level of branderpreneurship mindset, the higher the intensity, and the lower the level, the lower it will be.